Indigenous Language Impediment in English Speaking Setting: A Case Study of Thai EFL Learners - Salsabiil, Aqilah; Yenni Hasnah (Journal of English Development, 2026)
This study explores the ongoing issue of L1 interference from native Thai phonology impacting English speaking skills in Thai EFL students. Even with continuous formal English teaching, the native language still affects learners’ pronunciation precision in EFL speaking activities. Using a qualitative case study design, the study was carried out with junior high school students at Nida Suksasat School in Satun, Thailand. Data were gathered via classroom observations and video-recorded discussions on the grammatical subject “Have Got” and examined using phonological characteristics consistently disrupt that Thai phonological characteristics consistently disrupt English pronunciation, especially via sound substitution and sound alteration, even during rehearsed speaking tasks. This study adds to EFL studies by offering empirical proof of sustained phonological transfer in regulated speaking situations, underscoring that memorization fails to remove L1 impact. From a pedagogically, the findings highlight the significance of context-aware pronunciation teaching and phonological awareness-focused methods to reduce the impact of indigenous language interference in Thai EFL speaking classes.